Laparoscopic Tenckhoff catheter insertion technique with Alken telescopic metal dilator in pediatric population - Situmorang, Gerhard Reinaldi; Alfarissi, Fekhaza; Raharja, Putu Angga Risky; Rodjani, Arry; Wahyudi, Irfan (Medical Journal of Indonesia, 2025)
BACKGROUND End-stage renal disease (ESRD) is a major public health concern worldwide, with peritoneal dialysis (PD) offering a key alternative to hemodialysis. Flow restriction due to catheter migration is a common complication, affecting 7–26% of patients with PD. This study aimed to reduce complications in pediatric patients by examining a novel laparoscopic Tenckhoff catheter insertion technique using an Alken telescopic metal dilator. METHODS In a prospective observational study conducted between September 2018 and October 2022, 33 pediatric patients with ESRD underwent laparoscopic Tenckhoff catheter insertion using a combination of laparoscopic and Seldinger techniques with Alken dilators. This approach involves rectus sheath tunneling using a nephrostomy puncture needle, wire insertion, and dilatation of up to 15 Fr using Alken telescopic metal dilators under laparoscopic guidance. Survival analysis was used to assess catheter survival and complication rates. RESULTS The mean (standard deviation [SD]) patient age was 11.92 (3.7) years, with a median follow-up of 21.3 months. Catheter survival was 84.8%, with 5 catheter withdrawals due to infections (4 cases) or obstruction (1 case). Early and late complications, including exit-site infection, peritonitis, and catheter obstruction, occurred annually at rates of 0.10, 0.03, and 0.02 episodes per patient, respectively. No pericatheter leakage occurred. CONCLUSIONS This novel laparoscopic Tenckhoff catheter insertion technique using an Alken telescopic metal dilator become a simple and minimally invasive method, and associated with high catheter survival and low complication rates. Therefore, further comparative studies are recommended.